The effect of hydroalcoholic extract of Achillea eriophora DC. on blood pressure of anaesthetized male rat - Anvari, Sohrab; Bahaoddini, Aminollah; Moein, Mahmoodreza; Khosravi, Ahmad Reza (Technische Universität Dortmund, 2016)
Achillea eriophora (Asteraceae) is a medicinal plant commonly used in Iran. This study was performed to determine the cardiovascular effects of hydroethanolic extract of A. eriophora (HEAE) and the underlying mechanisms in anaesthetized rats. The acute effects of intravenous (i.v.) administration of different doses of HEAE (40, 50, 60, 80 mg/kg), and its probable interaction with cholinergic and nitrergic systems were investigated in the presence of ACh and NOS blocker (L-NAME) as well as ethanol (HEAE solvent in sham group). Intravenous administration of different doses of HEAE induced hypotension. HEAE (60 mg/kg) significantly reduced mean arterial blood pressure (MAP), systolic arterial blood pressure (SBP) and diastolic arterial blood pressure (DBP)compared to control rats that treated with ethanol only, but no change in heart rate (HR) was seen in both groups. The results showed significant decrease in MAP, SBP, DBP and increase of HR in the presence of HEAE plus ACh (10 μg/kg) compared to when ACh was injected alone. Finally i.v. administration of HEAE, significantly reduced MAP and DBP in L-NAME (5 mg/kg) treated animals, while bradycardic responses to L-NAME were not significantly changed by HEAE. It can be concluded that Achillea eriophora induced hypotensive effect via lowering total peripheral resistance and cardiac output that may be synergist with cholinergic and independent of nitrergic system.
EXCLI Journal;Vol. 15, 2016
Keywords: Achillea eriophora; hypotension; cholinergic system; nitrergic system; 610